LINC00461/miR-4478/E2F1 feedback loop promotes non-small cell lung cancer cell proliferation and migration. Issue 2 (25th February 2020) - Meng, Qingxin; Liu, Ming; Cheng, Ruyi
Abstract: Non-small cell lung cancer (NSCLC) is a prevalent subtype of lung cancer, whose mortality is high. Long non-coding RNAs (lncRNAs) have caught rising attentions because of their intricate roles in regulating cancerization and cancer progression. Long intergenic non-protein coding RNA 461 (LINC00461) has recently shown oncogenic potential in several cancers, but the function of LINC00461 in NSCLC remains to be investigated. Our study planned to unveil the regulatory role of LINC00461 in NSCLC. It was validated that LINC00461 was highly expressed in NSCLC tissues and cell lines and exhibited prognostic significance. Furthermore, LINC00461 expression in advanced stage was much higher than in early stage. Loss-of-function experiments suggested that LINC00461 knockdown impaired cell proliferation, migration, and epithelial-to-mesenchymal transition (EMT). Subcellular fractionation revealed the predominant location of LINC00461 in cytoplasm. Mechanistically, LINC00461 up-regulated E2F transcription factor 1 (E2F1) expression through sponging miR-4478. Besides, E2F1 bound to the promoter of LINC00461 to induce its transcription. Finally, rescue experiments verified that LINC00461 aggravated proliferation, migration, and EMT through targeting miR-4478/E2F1 axis. In consequence, the present study illustrated that LINC00461/miR-4478/E2F1 feedback loop promoted NSCLC cell proliferation and migration, providing a new prognostic marker for NSCLC.